The Influence of Hybrid Learning Model on Students’ Learning Attitudes in English Subject - Azmi Radjulani; Andi Nurwati (English Education Department, 2024)
This research aims to determine the influence of the hybrid learning model on students' learning attitudes in English language learning and examine the students’ learning attitudes in English language learning using the hybrid learning model. The study utilize a mixed-methods approach with a concurrent embedded design, employing questionnaires, interviews, and documentation as data collection techniques. The result of the study indicate that the hybrid learning model in English language learning influences students’ learning attitudes, with a coefficient of determination (R-squared) value of 0.299. This implies that the hybrid learning model accounts for 29.9% of the variance in students’ learning attitudes, while the remaining 70.1% is influenced by other unexplored variables. The implementation of the hybrid learning model at MTs.N 1 Kabupaten Gorontalo takes place during the transition period from full online learning to limited face-to-face learning, where students are scheduled to come to school. Students learning attitudes in the hybrid learning model exhibit both positive and negative aspects. Additionally, there is a special class in the school where many students display positive learning attitudes. However, it should be noted that students who are not part of the special class can still possess positive learning attitudes.